Software development by integrating the integrated value engineering (VE) and boothroyd design for assembly(DFA - Hasrol Nizam, Md. Hasan (2008)
In the current tough competition of the global industries, the companies all over the world are trying to reduce the cost of product via design, development and manufacturing concurrently making profit. Value Engineering (VE) and Design For Assembly (DFA) is an alternative to solve this problem. Through the concept of VE and DFA the designed product could be manufactured at the lower cost and fast to reach market. By combination of VE and DFA philosophy, the software that developed by using Microsoft Visual Basic 6.0 has fully done. The result of this research is software named VE-DFA. This software able to help the designer to choose and selected the best and effective design by referring to the highest design efficiency. Using Wira Driver Seat as case study, experimental results of this research show that the actual value of design efficiency is equal to 4.4 and by using VE-DFA software the result is equal to 4.32. Actual value is determined by using DFMA software. The results show that, there are close difference between actual value and value from VE-DFA software. Another analysis has been done to prove that the value of design efficiency is appropriate to the actual value using stapler and Computer Mouse as case study. For the stapler analysis, the actual value of efficiency is 33.2 and VE-DFA value is 31.02 and for computer mouse analysis the actual and VE-DFA value is equal to 28.25 and 26.17. Therefore, it can be concluded that, this software is valid in terms of its design efficiency.